Targeted therapy with Poly(ADP-ribose) polymerase (PARP) inhibitors for the treatment of solid tumours - Faustyna Piędel; Agata Agnieszka Rocka; Klaudia Daria Szumna; Dominika Katarzyna Madras; Patryk Piotr Jasielski (Kazimierz Wielki University, 2020)
Introduction: According to the National Cancer Register in Poland, the number of cancers including breast cancers has more than doubled in the past three decades. Poly(ADP-ribose) polymerase (PARP) inhibitors lead to the death of cells with a BRCA1/2 mutation. The use of PARP inhibitors has increased significantly over the last 5 years. Objective: This article summarizes the current knowledge about the safety and clinical  efficacy of PARP inhibitors in the treatment of solid tumors. Abbreviated description of the state of knowledge: PARP inhibitors have been used in the standard treatment of ovarian cancer. Three of them: Olaparyb, Rucaparyb and Niraparyb have indications for maintenance treatment in recurrent platinum-sensitive ovarian cancer. Olaparib and Weliparib are used to treat breast cancer patients. Research shows that the use of Olaparib in breast cancer patients has reduced tumours size as much as around 60% of women with BRCA mutation. The combination of veloparin with carbolatin and paclitaxel was associated with a longer mean survival period than chemotherapy alone in treatment of non-small cell lung cancer(NSCLC). In addition, there are studies showing the benefits of PARP inhibitor therapy in prostate cancer. Olaparyb in combination with abiraterone shows greater clinical efficacy in patients with castration-resistant prostate cancer compared alone abiraterone. Conclusions: FDA approval of new PARP inhibitors is a promising method for more effective treatment of the most common cancers in the world. In the future further research may lead to a better definition of the patient group benefiting most from PARP inhibitor therapy.